Clinicopathologic characteristics of epithelial ovarian tumours in Ile-Ife, Nigeria - AO Anjorin; GO Omoniyi-Esan; OO Odujoko; AO Anjorin (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2020)
Background: Epithelial ovarian tumours (EOT) have complex clinicopathologic characteristics and biological behaviours. There are benign, borderline and malignant ovarian tumours and the commonest ovarian tumours in many regions are of epithelial origin. Many studies have described the histomorphological characteristics of the tumours. Objective: To describe the clinical and histopathological features of epithelial ovarian tumours. Methods: This was a retrospective review of the histopathology reports of all epithelial ovarian tumours specimens submitted to the Department of Morbid Anatomy and Forensic Medicine, Obafemi Awolowo University Teaching Hospital, Ile-Ife from January 2005 to December 2014. The EOT cases were described in terms of age, clinicopathological characteristics and distribution of histological types. Results: The frequencies of benign, borderline and malignant EOTs were 41.2%, 3.9% and 54.9% respectively and the patients were aged 23 to 94 years (mean 46.5±2.6 years). The majority of cases were often asymptomatic. Conclusion: Abdominal swelling was the most common presenting complaint while serous ovarian tumours were the most preponderant histological types.